Correction: Xie et al. Investigating Fire Collapse Early Warning Systems for Portal Frames. Buildings 2025, 15, 296 - Ming Xie; Fangbo Xu; Zhangdong Wang; Li’e Yin; Xiangdong Wu; Mengqi Xu; Xiang Li (Buildings)
Insert the reference [...]